ChemInform Abstract: Advances in Gold Catalysis and Understanding the Catalytic Mechanism. Issue 50 (November 2016) - Ishida, Tamao; Koga, Hiroaki; Okumura, Mitsutaka; Haruta, Masatake
Abstract: Review: 109 refs.